Trust Establishment For Detecting Aggressor Nodes And Improving Route Stability In Wsn-Iot - et. al., L. Sasirega, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Wireless Sensor Network (WSN) constructing a secure routing between nodes is a difficult task. Removing the aggressor nodes highly improves the network performance and therefore an Efficient Routing through Node Stability Trust Evaluation is proposed here. Here the trusted nodes are detected through their node stability function with their hybrid trust values that includes direct trust and recommended trust values. Once the trusted nodes are identified then the route stability function is applied to detect the reliable routes. Route stability functions calls the route maintenance whenever the transmission requires re-routing. To reduce the re-routing process the reliable routes are detected by selecting link stability and trusted energy efficient nodes before transmitting the data. Simulation analysis is carried out and the comparisons are done with the conventional protocols.